2012
DOI: 10.1007/s10561-012-9341-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of autologous serum as an alternative to fetal bovine serum in adipose-derived stem cell engineering

Abstract: In cell culture, medium supplemented with fetal bovine serum is commonly used, and it is widely known that fetal bovine serum supplies an adequate environment for culture and differentiation of stem cells. Nevertheless, the use of xenogeneic serum can cause several problems. We compared the effects of four different concentrations of autologous serum (1, 2, 5, and 10%) on expansion and adipogenic differentiation of adipose-derived stem cells using 10% fetal bovine serum as a control. The stem cells were grafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…[41], in which equine ASCs cultured with autologous serum proliferate less than with FBS. Differently, our results are in contrast with data obtained with human ASCs, in which it has been shown that the use of autologous serum favors or does not influence ASCs proliferation [21,51,52]. Nevertheless, Kurita et al [53] showed that among four human ASC populations, only one proliferates faster when cultured with autologous serum.…”
Section: Discussioncontrasting
confidence: 99%
“…[41], in which equine ASCs cultured with autologous serum proliferate less than with FBS. Differently, our results are in contrast with data obtained with human ASCs, in which it has been shown that the use of autologous serum favors or does not influence ASCs proliferation [21,51,52]. Nevertheless, Kurita et al [53] showed that among four human ASC populations, only one proliferates faster when cultured with autologous serum.…”
Section: Discussioncontrasting
confidence: 99%
“…With 15% SCC supplementation, the hMSC yield, replicative capacity, and cell viability were comparable with those observed with the commercial medium, indicating that normal use of SCC as a substitute for FBS can be performed reliably. A previous study has also tested cell growth and differentiation capacity with various concentrations of autologous serums versus FBS [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that AS outperforms FBS for the cultivation of human T cells [20] as well as human articular chondrocytes [21]. AS and AP have been shown to be suitable supplements also for the expansion of various stem cells obtained from different origins without adversely affecting their differentiation capacity [22][23][24][25]. However, subsequent studies have turn out that the replacement of FCS by AS or AP is not always effective.…”
Section: Discussionmentioning
confidence: 99%